P1-S2.08 Geography, mobility, work venue, and sexually transmitted infections among 4100 female sex workers in 20 cities in Peru. (10th July 2011) - Mejia, C; Campos, P; Carcamo, C; Garcia, P; Hughes, J; Martin, D; Garnett, G; Holmes, K
Abstract : Objectives: To estimate and compare prevalences of five STI Chlamydia trachomatis (CT) Neisseria gonorrhoeae (NG), Trichomonas vaginalis (TV), T pallidum (syphilis), and HIV infection for female sex workers (FSW) according to home geographic region and mobility, and to identify other STI risk factors. Methods: Data on geographic region, internal mobility (defined as having engaged in sex work in >2 Peruvian cities in the previous 12 months or was working away from their home city at enrolment), sex work characteristics, sociodemographics and, behaviours, were collected together with vaginal and blood specimens from 4100 FSW in 20 Peruvian cities. Multivariate analysis identified factors associated being infected with any of the five STI. Results: FSW from the jungle region had higher prevalences of CT, NG, TV, syphilis, and HIV than FSW from the coastal or highlands regions. In univariate analysis, having worked in >2 more cities or working away from home were significantly negatively associated with having any STI. In multivariate analyses the mobility status variable showed a trend towards protective associations; neither remained significant. Risk of any STI was significantly and independently associated with bar/nightclub or street work, being from the jungle region, and not completing high school. Conclusion: Findings suggest that internal mobility does not increase risk among Peruvian FSW. Preventive interventions should focus on FSW from the jungle region, those working in bars/nightclubs or on the street and those lacking secondary education to halt the spread of STI among FSW and, presumably, to the general population.